Viabilidade da cultura Cnidoscolus quercifolius POHL para produção de Biodiesel no semiárido nordestino - Bezerra, Priscila Daniele Fernandes (2011)
The northeastern semiarid is a region that presents a serious picture stagnation or slowness of the economic growth, beyond the presence of social pointers below of the averages national and regional. The half-dryness conditions become the improper region for many agricultural cultures, what it affects the local populations directly, as well as the economy that is based mainly on agriculture. Cnidoscolus quercifolius Pohl, popularly know as favelone is a native species of the semiarid region that withholds great potential for the development of the region in virtue of its multiple uses. Being an oleaginous, its production in familiar farmings makes with that biodiesel either for the misery an important alternative eradication for the possibility of occupation of enormous contingents of people. The present study it aims at to evaluate the germination of the faveleira without thorns under conditions of water and saline stresses, main stresses which the vegetal species of the semiarid one are submitted; beyond verifying the acceptance of the species for agriculturists of a cooperative in the city of Apodi/RN. The methodology used for germination corresponds to using treatments with polyethylene glycol and sodium chloride to assess water and salt stress respectively, being held in rolo. O system approach used for the verification of acceptance of faveleira was the use of interview with farmers cooperative in the study area determined. In this direction it was verified that the faveleira is a resistant species the conditions of drought and salinity of the ground, factor of great relevance, since one is about a species with high added value, making possible the development for the semiarid region. It was verified that the agriculturists are favorable the introduction of the faveleira and reveal receptive the idea to cultivate a species with potential for production of biodiesel